Listening to battered women: a survivor-centered approach to advocacy, mental health and justice - Goodman, Lisa A. (Psychology of women book series, 2008)
The need for continued reform : the broad scope and deep impact of intimate partner violence -- The advocacy response -- The mental health system response -- The justice system response -- A critical analysis of system responses : the importance of voice, community, and economic empowerment -- Recommendations for future reform